(untitled) (Malaysian Journal of Learning and Instruction, 2018)
Purpose – This study was designed to create platforms to train students in higher education to be caring and responsible citizens. This was an extension mission that aimed to tap into the expertise of academe and its knowledge to help the community. Based on the framework of academic of community empowerment, the researchers measured the long-term impact of a 44-month community extension program in the Philippines. The extension program described in this study was implemented between March 2009 and December 2015 to address the capacity-building needs of a low-income community. This paper highlights some key development activities which includes partnership with local government, training needs assessment through grassroots-level participation and design of practical education-training programs. Methodology – The study followed a descriptive research design. The Community Outcome Scale (COS) was developed to measure perceived knowledge, attitude, and lifestyle of the beneficiaries. Fifty-four community residents were purposively selected based on their attendance to the community-based education and training programs. The ANOVA method with post hoc analysis was employed to determine the differences between perceived knowledge, attitude, and lifestyle among residents, stratified according to the degree of completion of the training programs. Findings – There was a moderate improvement in community knowledge, attitude, and lifestyle based on the survey which was performed one and a half years after the completion of the extension programs. Based on the results, improved long-term outcomes were noted only amongst the regular and occasional participants. Significance – There is an increasing appreciation of the impact of higher education extension in the teaching and learning process as students apply their disciplinary knowledge to help address real-world problems. This work may be of interest to higher education institutions (HEIs) which are designing community extension programs with optimized societal outcomes.